Cover Picture: Re‐examination of the C6Li6 Structure: To Be, or not To Be Symmetric (Chem. Eur. J. 38/2013). Issue 38 (12th September 2013) - Moreno, Diego; Martínez‐Guajardo, Gerardo; Díaz‐Celaya, Andrés; Mercero, José M.; de Coss, Romeo; Perez‐Peralta, Nancy; Merino, Gabriel
<x xml:space="preserve">Abstract</x> The potential energy surface and fluxionality of C6Li6 is discussed by G. Moreno et al. in their Full Paper on page 12668 ff., providing a new structure of C6Li6, which can be described as three C22− fragments, strongly aggregated through lithium bridges. At high temperatures fluxionality is perceived instead of dissociation. At 600 and 900 K, Born–Oppenheimer molecular dynamics simulations show that the lithium mobility is high, indicating that the cluster behaves like a liquid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>